2008
DOI: 10.1088/0953-8984/20/33/335105
|View full text |Cite
|
Sign up to set email alerts
|

A combined neutron and x-ray diffraction study of short- and intermediate-range structural characteristics of Ge–As sulfide glasses

Abstract: A combination of neutron and x-ray diffraction has been employed to study the compositional dependence of the atomic structures of GexAsxS100−2x glasses with S concentration varying between 33.3 and 70.0 at.%. The nearest-neighbor coordination numbers of Ge and As atoms are always found to be 4 and 3, respectively, irrespective of the glass composition. Ge and As atoms have primarily heteropolar bonding to S atoms in stoichiometric and S-excess glasses with x≤18.2. Low and intermediate levels of deficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 32 publications
5
37
1
Order By: Relevance
“…This structural scenario is in excellent agreement with the results of a previous Ge and As K-edge EXAFS spectroscopic study of short-range order in ternary Ge 0.1 As x Te 0.9 − x glasses with x = 0.15, 0.20, 0.46 and 0.54 that indicated the presence of Ge/As-Ge/As bonds even in Te-excess glasses [14]. It should also be noted here that glass compositions along similar tie lines in Ge-As-S and Ge-As-Se ternary systems do not show any evidence of such gross violation of shortrange chemical order [11,12,19,21,22]. Violation of chemical order in Ge-As-Te glasses may be related to the significantly higher metallicity of Te compared to S or Se.…”
Section: 2mentioning
confidence: 56%
See 1 more Smart Citation
“…This structural scenario is in excellent agreement with the results of a previous Ge and As K-edge EXAFS spectroscopic study of short-range order in ternary Ge 0.1 As x Te 0.9 − x glasses with x = 0.15, 0.20, 0.46 and 0.54 that indicated the presence of Ge/As-Ge/As bonds even in Te-excess glasses [14]. It should also be noted here that glass compositions along similar tie lines in Ge-As-S and Ge-As-Se ternary systems do not show any evidence of such gross violation of shortrange chemical order [11,12,19,21,22]. Violation of chemical order in Ge-As-Te glasses may be related to the significantly higher metallicity of Te compared to S or Se.…”
Section: 2mentioning
confidence: 56%
“…Recently there has been a renewed surge of interest in telluride glasses as amorphous Ge-Sb-Te thin film materials exhibit interesting phase change phenomena induced by optical or electrical switching that can be exploited in rewritable optical data storage and in non-volatile electronic memory applications [5][6][7][8][9]. Consequently, the structure-property relationships in ternary chalcogenide glasses have received a great deal of research attention in recent years [10][11][12][13][14][15][16][17][18][19][20][21][22]. The results of these studies have shown that in ternary Ge-As-S/Se glasses the nearest-neighbor coordination numbers of Ge and As atoms are always 4 and 3, respectively, regardless of glass composition.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This is despite the analysis of quenched glass structures that indicate atomic to nanometer scale structural heterogeneity must occur in the liquid state. [4][5][6][7] Silica is classified as a strong liquid with an Arrhenius viscosity-temperature relation and only subtle differences occur between the liquid and glass structures. 8,9 In contrast CaO-SiO 2 liquids can be considered fragile based on viscosity measurements 10,11 and consequently larger structural rearrangements are likely to be necessary to form a glass.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,13 The FSDPs have been observed in the structure function S(q) obtained from x-ray and neutron scattering in glasses, melts and liquids with intermediate range order. 5,6,[23][24][25][26] The FSDP is frequently observed for molten metal halides, 5 mixtures of tetrahedral glass-formers 25 and binary selenides. 26 For these systems, the FSDPs are typically observed for magnitudes of the scattering vector in the range from 0.9 ≤ q ≤ 1.5 Å −1 .…”
mentioning
confidence: 99%